Suveræne livsytringer og kredsende tanker og følelser – en kritisk udfoldelse af deres karakteristika - Rabjerg, Bjørn (Dansk Teologisk Tidsskrift, 2014)
The “sovereign expressions of life” and the “encircling thoughts and emotions” are phenomena at the core of K.E. Løgstrup’s metaphysics and ethics. However, their respective characteristics have not been fully developed until now. In this article these characteristics are examined through a systematic analysis of both types of phenomena in which their differences are exposed. They are both spontaneous, but the encircling thoughts and emotions are found to be our own, self-containing, destructive and reactive thoughts and emotions – whereas the sovereign expressions of life are created and given, definitive, consummated, sovereign, unconditioned, identity creating and anonymous possibilities within interdependent life; as such they possess the power to release us from the confinement of our own thoughts and emotions.